2017
DOI: 10.1016/j.jalz.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

The Alu neurodegeneration hypothesis: A primate‐specific mechanism for neuronal transcription noise, mitochondrial dysfunction, and manifestation of neurodegenerative disease

Abstract: It is hypothesized that retrotransposons have played a fundamental role in primate evolution and that enhanced neurologic retrotransposon activity in humans may underlie the origin of higher cognitive function. As a potential consequence of this enhanced activity, it is likely that neurons are susceptible to deleterious retrotransposon pathways that can disrupt mitochondrial function. An example is observed in the TOMM40 gene, encoding a β-barrel protein critical for mitochondrial preprotein transport. Primate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 99 publications
4
55
0
Order By: Relevance
“…298 is mitochondrial dysfunction (Lin and Beal 2006; Rugarli and Langer 2012; Gottschalk et al 2992014;Petschner et al 2017). However, we have previously shown that mitonuclear genes are 300 enriched with Alu elements when compared to random(Larsen et al 2017), which is 301 consistent with earlier observations regarding the non-random insertion of Alu elements into 302 genes associated with transcriptionally active regions of the genome(Grover et al 2003; de 303 Andrade et al 2011). Thus, it is likely that Alu-mediated gene regulatory processes are 304 actively influencing mitonuclear gene expression, regulation, and protein function through 305 the pathways discussed above and reviewed in(Chen and Yang 2017).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…298 is mitochondrial dysfunction (Lin and Beal 2006; Rugarli and Langer 2012; Gottschalk et al 2992014;Petschner et al 2017). However, we have previously shown that mitonuclear genes are 300 enriched with Alu elements when compared to random(Larsen et al 2017), which is 301 consistent with earlier observations regarding the non-random insertion of Alu elements into 302 genes associated with transcriptionally active regions of the genome(Grover et al 2003; de 303 Andrade et al 2011). Thus, it is likely that Alu-mediated gene regulatory processes are 304 actively influencing mitonuclear gene expression, regulation, and protein function through 305 the pathways discussed above and reviewed in(Chen and Yang 2017).…”
supporting
confidence: 84%
“…Thus, it is likely that Alu-mediated gene regulatory processes are 304 actively influencing mitonuclear gene expression, regulation, and protein function through 305 the pathways discussed above and reviewed in(Chen and Yang 2017). Knowing this, the 306 dysregulation of epigenetic Alu regulatory pathways is a plausible source for mitochondrial 307 stress and dysfunction, with the CNS being particularly vulnerable(Larsen et al 2017). Such 308 a mechanism could contribute to the initial activation of complex mitochondrial stress 309 pathways and incipient neuronal stress associated with sporadic neurologic disorders (e.g., 310inflammation, immune response, mitophagy, etc.).…”
mentioning
confidence: 99%
“…A number of aged mouse lemurs do show Alzheimer's‐like symptoms, such as brain atrophy, amyloid plaques, and neurofibrillary tangles. Thus, mouse lemurs are the best available primate model to understand brain aging and disease . Although relatively little work has been produced, there is indication that dwarf lemurs also show reversible phosphorylation between cycles of hibernation, which can prove highly relevant to the field of brain degenerative conditions …”
Section: What Can Hibernation Studies In Primates Tell Us About Metabmentioning
confidence: 99%
“…Thus, mouse lemurs are the best available primate model to understand brain aging and disease. 95,97,98 Although relatively little work has been produced, there is indication that dwarf lemurs also show reversible phosphorylation between cycles of hibernation, which can prove highly relevant to the field of brain degenerative conditions. 99 Another biomedical approach related to neurodegenerative diseases is examining the role of melatonin as effective protection against oxidative stress and using it as co-treatment of Parkinson's and other neurodegenerative conditions.…”
Section: Wh a T Ca N H I Ber N At I On S T U Di E S I N P R I M At mentioning
confidence: 99%
“…Also, the difficulty in developing novel interventions to detect [1–57], delay [58–69], or halt disease progression continues to be an important hurdle. The well‐recognized public health and economic imperative [70–83] posed by the disease continues to be an important motivator to communicate new knowledge across multiple disciplines that will help increase the likelihood of unlocking the complexity of neurodegeneration [84–90] associated with many dementing illnesses.…”
mentioning
confidence: 99%